Solvent-controlled base-free synthesis of bis(trifluoromethyl)-cyclopropanes and -pyrazolines via cycloaddition of 2-trifluoromethyl-1, 3-enynes with 2, 2, 2-trifluorodiazoethane. Issue 25 (15th June 2022) - Ma, Zhihong; Deng, Yupian; He, Jingjing; Cao, Song
Abstract : A highly efficient solvent-controlled synthesis of bis(trifluoromethyl)cyclopropanes and bis(trifluoromethyl)pyrazolines via a [2 + 1] or [3 + 2] cycloaddition reaction of 2-trifluoromethyl-1, 3-conjugated enynes with CF3 CHN2 was developed. Abstract : A highly efficient solvent-controlled synthesis of bis(trifluoromethyl)cyclopropanes and bis(trifluoromethyl)pyrazolines via a [2 + 1] or [3 + 2] cycloaddition reaction of 2-trifluoromethyl-1, 3-conjugated enynes with CF3 CHN2 was developed. The reactions of 2-trifluoromethyl-1, 3-conjugated enynes with CF3 CHN2 proceeded smoothly under transition-metal and base-free conditions, affording the expected cycloaddition products in good to excellent yields. When DMAc ( N, N -dimethylacetamide) was used as the solvent, bis(trifluoromethyl)pyrazolines were obtained; however, in contrast, bis(trifluoromethyl)cyclopropanes were formed by changing the solvent from DMAc to DCE (1, 2-dichloroethane).